PENGEMBANGAN MODUL AJAR BERBASIS KUE TRADISIONAL BANJAR UNTUK PEMAHAMAN KONSEP GEOMETRI DI KELAS V SD - Ella Aulia; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract This research aims to produce a teaching module, analyze its feasibility and see teacher and student responses to a teaching module based on traditional Banjar cakes for understanding geometric concepts. This research design uses development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this research were fifth grade students at SD Negeri 104261 Sukajadi. The tools used in this research were material expert validation questionnaire sheets and teacher response and student response questionnaire sheets. Based on the results of the assessment carried out by the material expert validator, the results of the material expert assessment were 90% with the criteria